UWAGI O PROCESIE CHRYSTUSA - Miglietta, Massimo (Zeszyty Prawnicze, 2017)
Remarks on Christ’s Prosecution Summary The subject of the analysis is the prosecution of Jesus of Nazareth, considered by some scholars as the biggest felony committed w ithin the limits of law, by others - as the proceedings conducted w ithout a breach of the charged person’s rights. The author, making use of the sources of law and the Bible researchers allowing to reconstruct the original course of the events, tries to answer a question whether and to what extent the Jews together with the Romans participated in Christ’s sentencing for capital punishm ent and what their responsibility is. The author does not share the view that the proceedings were divided into two separate ones: Jewish and Roman, viz., that the hearing before Sanhedrin was of a religious character and before Pontius Pilat - political. He is certain however that the proceedings had two stages: the investigation during which Jesus was heard by sanhedrin and the court one when Pontius Pilat issued a verdict. The author does not ponder over the fairness of Christ’s prosecution, he only tries to explain whether it was in accordance with the contemporary law. in his opinion the law was not breached, nevertheless, he leaves the question of the judges’ individual liability open.